Social Reforms in Brazil: Criticism of the Institutionalization of BolsaFamília Program - Carolina Alves Vestena (Sortuz)
In this article I discuss preliminary outcomes of an ongoing research that focuses on the process of institutionalization of the BolsaFamília program (BFP), a Brazilian conditional cash transfer policy launched in 2003. Since then this policy has achieved considerable results in regard to the decrease of poverty and fight against hunger. Nevertheless its potential to change social structures of inequality in the country is still under discussion. Considering the program in the Latin American context, the aim of this paper is to bring together a set of studies conducted in the field of Law and Development that analyses the role of legal regulation within BFP and critical inputs from the Latin American social thought in order to offer an alternative research agenda about the role of law in social reforms.